2016
DOI: 10.1186/s10194-016-0624-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant behavioral endpoints in a recurrent nitroglycerin migraine model in rats

Abstract: BackgroundThis research sought to further validate the rat nitroglycerin (NTG) migraine model by comparing the effects of single versus recurrent NTG episodes on behavioral endpoints that mirror ICHD-3 diagnostic criteria for migraine, and to determine if the altered behavioral endpoints are reduced after administration of sumatriptan.MethodsSeparate cohorts of rats were administered NTG (10 mg/kg/2 ml) or saline (Experiment 1: single injection; Experiment 2: repeated injections; Experiment 3: repeated injecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 27 publications
3
57
0
Order By: Relevance
“…We have tested the effects of chronic NTG in a warm water tail immersion assay (46-48°C) (Pradhan, Smith, Zyuzin, et al, 2014), and we see similar changes in pain sensitivity. In addition, others have reported that acute and chronic NTG can produce light aversion, which models the photophobia associated with migraine (Farajdokht, Babri, Karimi, & Mohaddes, 2016; Markovics et al, 2012; Sufka et al, 2016). Taken together, multiple lines of evidence indicate that NTG administration in rodents can be used to effectively model migraine-associated behaviors.…”
Section: Commentarymentioning
confidence: 99%
“…We have tested the effects of chronic NTG in a warm water tail immersion assay (46-48°C) (Pradhan, Smith, Zyuzin, et al, 2014), and we see similar changes in pain sensitivity. In addition, others have reported that acute and chronic NTG can produce light aversion, which models the photophobia associated with migraine (Farajdokht, Babri, Karimi, & Mohaddes, 2016; Markovics et al, 2012; Sufka et al, 2016). Taken together, multiple lines of evidence indicate that NTG administration in rodents can be used to effectively model migraine-associated behaviors.…”
Section: Commentarymentioning
confidence: 99%
“…A number of studies have used depression of activity (e.g., locomotor activity, feeding, rearing) to assess pain resulting from headache in humans [18] and rodents [7, 9, 17, 20, 28]. The problem with these studies is that assessment was limited to 60 min or less making it impossible to quantify the full duration and magnitude of the migraine.…”
Section: Introductionmentioning
confidence: 99%
“…CADASIL and FASP animals received serial NTG injections on Days 0, 2, 4, 6, and 8 (the day of the gastrointestinal motility procedure), similar to prior reports in mice 43 and rats, 44,45 with the intent to maximize the effects of pretreatment with NTG. CADASIL and FASP animals received serial NTG injections on Days 0, 2, 4, 6, and 8 (the day of the gastrointestinal motility procedure), similar to prior reports in mice 43 and rats, 44,45 with the intent to maximize the effects of pretreatment with NTG.…”
Section: Methodsmentioning
confidence: 99%